ANALISIS TATA CARA PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPH PASAL 23 DAN PAJAK PERTAMBAHAN NILAI PT “X” - AINA MARSELINA; RIAN SUMARTA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The research is conducted with three basic purpose. The first purpose of this research is to find out the procedures of calculation, payment, reporting and recording of income tax article 23 and value added tax at PT.